Analysis of an event of parametric rolling onboard RV polarstern based on shipborne wave radar and satellite data - Bruns, Thomas; Lehner, Susanne; Li, Xiao Ming; Hessner, Katrin; Rosenthal, Wolfgang (IEEE Journal of Oceanic Engineering, 2011)
During the Antarctic summer season 2008/2009 the wave radar system WaMoS II was installed onboard of the German research vessel Polarstern. The purpose was to collect quasi-in situ data for the comparison with satellite-borne SAR and altimeter instruments (Envisat, TerraSAR-X, Jason). The experiment was part of the German research project DeMarine-Security. On 7 March 2009 in the central South Atlantic Ocean, Polarstern was heading towards Punta Arenas against a rough cross sea. In the night, a sudden event of heavy rolling, i.e., an oscillation about its length axis, hit the vessel and lasted for a few minutes. Using WaMoS II data, as well as ENVISAT and wave model data, we investigate the conditions under which the event occurred. It is shown that the rolling was caused by a parametric resonance when the period of encounter came close to one half of the vessels's natural rolling period. We conclude that an onboard wave radar can be helpful in diagnosing and forecasting critical conditions. © 2011 IEEE.
CRIS-Team Scopus Importer:2024-03-18
Keywords: Ocean surface waves; parametric rolling; shipborne wave radar; synthetic aperture radar